Immunomodulatory Properties of Bone Marrow Mesenchymal Stem Cells from Patients with Amyotrophic Lateral Sclerosis and Healthy Donors - Javorkova, Eliska; Matejckova, Nicole; Zajicova, Alena; Hermankova, Barbora; Hajkova, Michaela; Bohacova, Pavla; Kossl, Jan; Krulova, Magdalena; Holan, Vladimir (Journal of neuroimmune pharmacology, 2019)
Pathogenesis of amyotrophic lateral sclerosis (ALS) involves several mechanisms resulting in a shift from a neuroprotective to a neurotoxic immune reaction. A promising tool for ALS treatment is represented by mesenchymal stem cells (MSCs), which possess both regenerative potential and immunomodulatory properties. In this study, we aimed to compare the immunomodulatory properties of MSCs isolated from the bone marrow of patients suffering from ALS and healthy donors. Moreover, the influence of proinflammatory cytokines on the immunoregulatory functions of MSCs was also evaluated. We found that MSCs from ALS patients and healthy donors comparably affected mitogen-stimulated peripheral blood mononuclear cells and reduced the percentage of T helper (Th)1, Th17 and CD8+CD25+ lymphocytes. These MSCs also equally increased the percentage of Th2 and CD4+FOXP3+ T lymphocytes. On the other hand, MSCs from ALS patients decreased more strongly the production of tumour necrosis factor-α than MSCs from healthy donors, but this difference was abrogated in the case of MSCs stimulated with cytokines. Significant differences between cytokine-treated MSCs from ALS patients and healthy donors were detected in the effects on the percentage of CD8+CD25+ and CD4+FOXP3+ T lymphocytes. In general, treatment of MSCs with cytokines results in a potentiation of their effects, but in the case of MSCs from ALS patients, it causes stagnation or even restriction of some of their immunomodulatory properties. We conclude that MSCs from ALS patients exert comparable immunomodulatory effects to MSCs from healthy donors, but respond differently to stimulation with proinflammatory cytokines. Graphical Abstract Treatment of mesenchymal stem cells (MSCs) with cytokines results in a potentiation of their effects, but in the case of MSCs from amyotrophic lateral sclerosis (ALS) patients, it causes stagnation (an equal reduction of the percentage of CD8+CD25+ T lymphocytes) or even restriction (no increase of proportion of CD4+FOXP3+ T lymphocytes) of some of their immunomodulatory properties. It means that MSCs from ALS patients exert comparable immunomodulatory effects to MSCs from healthy donors, but respond differently to stimulation with proinflammatory cytokines.
Keywords: Immunologic Factors; T-lymfocyty pomocné-indukující; Male; Immunomodulation; Middle Aged; Mesenchymal Stem Cells; CD4+FOXP3+ T lymphocytes; Tumor Necrosis Factor-alpha; mezenchymální kmenové buňky; leukocyty mononukleární; buňky kostní dřeně; cytokiny; Helper T lymphocytes; mužské pohlaví; imunomodulace; Amyotrophic lateral sclerosis; Proinflammatory cytokines; Amyotrophic Lateral Sclerosis; Leukocytes, Mononuclear; lidé; ženské pohlaví; Humans; zdraví dobrovolníci pro lékařské studie; TNF-alfa; Cytokines; imunologické faktory; Female; Bone Marrow Cells; lidé středního věku; amyotrofická laterální skleróza; Mesenchymal stem cells; Mitogens; T-Lymphocytes, Helper-Inducer; Healthy Volunteers; mitogeny